Increase in testosterone and cortisol one week after repeated exercise in a cold environment - Jaklová Dytrtová, Jana; Jakl, Michal; Jebavý, Radim; Máčová, Ludmila; Horníková, Daniela; Novák, František; Vodička, Petr; Navrátil, Tomáš; Bičíková, Marie; Elsnicová, Barbara; Žurmanová, Jitka; Galatík, František (Frontiers in Physiology, 2026)
IntroductionEffects of cold exposure on human physiology are mainly studied after exercise. Therefore, this study aims to investigate the effects of gradually increasing cold exposure and physical exercise on steroid levels, body composition, and other biochemical markers in healthy male athletes immediately after 5-day exercise in cold and after 7 days of recovery.MethodsHealthy male athletes (n = 12, aged 20.5 ± 1 year, height 181 ± 7.7 cm) were exposed to 5 days of outdoor physical training (2 °C–3 °C) with increasing intensity of exercise and cold exposure. Venous blood was collected, and body bioelectrical impedance measured before and after the 5-day experiment, and after 7-day recovery. Circulating levels of testosterone, cortisol, androstenedione, dehydroepiandrosterone sulphate, 17-hydroxyprogesterone, calcifediol, interleukin-6, C-reactive protein, and erythrocyte superoxide dismutase activity were analysed.ResultsOur data show a delayed effect of exercise in cold after 7 days of recovery in the total plasma levels of testosterone (56% increase vs. baseline) and cortisol (54% increase vs. baseline), with no difference immediately after physical training in cold. Bioelectrical impedance analysis showed a decrease in waist-to-hip ratio after the experiment, which normalised after 7 days. No significant changes were observed in Interleukin-6, C-reactive protein, or superoxide dismutase levels.ConclusionA 5-day period of daily exercise in a cold environment showed no immediate effects, but a potential to elicit adaptive changes delayed for up to 7 days, leading to a significant increase in steroid hormones, without changing the testosterone/cortisol ratio.